Social workers understanding of extended families position in child welfare in Lithuania, Chile and Norway - Oltedal, Siv; Studsrød, Ingunn; Naujanienė, Rasa; Guzmán, Carolina Muñoz (Journal of Comparative Social Work, 2020)
Child welfare services around the world deal with families and family complexities. The study from Chile, Lithuania and Norway explores how social workers define family and more specific the position of extended families within child welfare and thus indicate contextual differences and similarities. In the data collection, five focus groups were included: one Lithuanian (eight participants), two Chilean (with two and two participants) and two Norwegian groups (with seven and eight participants). The analysis reveals significant and thematic differences and similarities between the countries related to the fluid and varied concept of family. The results also show variations across contexts in which families that are targeted by the services, the involvement of children and nuclear and extended family members. A dilemma between children’s need to keep family bonds and the states responsibility to protect children, can be exemplified with the position of the extended family. We can identity a difference between Norway, with comprehensive state involvement that can be framed as they are dealing with a public family, and both Chile and Lithuania, which put more of an emphasis on problem-solving within families, and thus look at the family as more of a private sphere.